SOME RESULTS CONCERNING THE ANALYTIC REPRESENTATION OF CONVOLUTION - Reckovski, Vasko; Iseni, Egzona; Manova Erakovikj, Vesna (Matematichki Bilten, 2018)
In this paper we will prove some results concerning the analytic representation of the convolution of some functions and distributions.